2005
DOI: 10.1016/j.neuropsychologia.2004.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic–serotonergic imbalance contributes to cognitive and behavioral symptoms in Alzheimer’s disease

Abstract: Neuropsychiatric symptoms seen in Alzheimer's disease (AD) are not simply a consequence of neurodegeneration, but probably result from differential neurotransmitter alterations, which some patients are more at risk of than others. Therefore, the hypothesis of this study is that an imbalance between the cholinergic and serotonergic systems is related to cognitive symptoms and psychological syndromes of dementia (BPSD) in patients with AD. Cholinergic and serotonergic functions were assessed in post-mortem front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
146
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(156 citation statements)
references
References 46 publications
9
146
0
1
Order By: Relevance
“…The reduced 5-HT concentration in the present and previous (Mimica et al 2008) study in platelets, CSF (Tohgi et al 1992) and brain (Garcia-Alloza et al 2005) of patients in the late phase of AD would suggest the decrease in 5-HT synthesis. The main factors that influence 5-HT synthesis are plasma availability of its precursor tryptophan, and the activity of the rate-limiting enzyme tryptophan hydroxylase (TPH).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The reduced 5-HT concentration in the present and previous (Mimica et al 2008) study in platelets, CSF (Tohgi et al 1992) and brain (Garcia-Alloza et al 2005) of patients in the late phase of AD would suggest the decrease in 5-HT synthesis. The main factors that influence 5-HT synthesis are plasma availability of its precursor tryptophan, and the activity of the rate-limiting enzyme tryptophan hydroxylase (TPH).…”
Section: Discussionsupporting
confidence: 59%
“…Reduced TPH activity was found in some brain areas of patients with AD (Gottfries, 1990) that might be associated with a decrease in 5-HT synthesis (Garcia-Alloza et al 2005). It has been shown that tetrahydrobiopterin and folic acid are two cofactors necessary for TPH activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Serotonergic activity is implicated in cognitive function, and is proposed to interact with the cholinergic system to impact memory and attention. [7][8][9] Schultz et al 10 observed an association between increased phobic symptoms and lower global cognitive function in older adults, with a trend for this association to be exacerbated in those with the 5-HTT s allele. In healthy, nondepressed adults, Canli et al…”
Section: Introductionmentioning
confidence: 99%
“…These behavioral and psychological symptoms of dementia (BPSD) include hallucinations, delusions, aggressive behavior, over activity, anxiety and affective disturbances 1,2 . Current options for treating the cognitive symptoms associated with Alzheimer's are inadequate, giving urgency to the search for novel therapeutic strategies [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%